Evaluasi Usability Electronic Integrated Antenatal Care (e-iANC) - Hosizah Hosizah; Fachmi Tamzil; Mulyo Wiharto (Indonesian of Health Information Management Journal (INOHIM), 2020)
AbstractElectronic Integrated Antenatal Care (e-iANC) is a web-based application that can be used by midwives in antenatal care (ANC) data and information management. Currently, e-iANC is being developed so that it can be used in the public primary healthcare at sub-district level. To ensure that e-iANC is used by end users, it was needed to test e-iANC using the System Usability Scale (SUS) instrument. The e-iANC test had been conducted in a structured and accurate manner by using SUS’ ten statements on 22 purposive samples. The results obtained were 83.1 scores, which means that the e-iANC application was declared acceptable (acceptable) and good ratings in grade A and B. The e-iANC application could be developed and used as a tool for midwives in ANC.Keyword: Electronic Integrated Antenatal Care, e-iANC, System Usability Scale (SUS), midwifeAbstrakElectronic Integrated Antenatal Care (e-iANC) merupakan aplikasi berbasis web yang dapat digunakan bidan dalam manajemen data dan informasi pelayanan antenatal (ANC). Saat ini e-iANC sedang dikembangkan agar dapat digunakan dalam lingkup lebih luas yaitu di puskesmas tingkat kelurahan dan kecamatan. Untuk menjamin e-iANC dapat dimanfaatkan bidan sebagai pengguna akhir diperlukan pengujian menggunakan SUS’s instrument (System Usability Scale). Pengujian e-iANC telah dilaksanakan secara sistematis dan terukur secara akurat menggunakan 10 pernyataan untuk menilai sampel sebanyak 22 orang yang diambil secara purposive. Hasil pengujian e-iANC diperoleh skor penilaian 83,1 yang berarti aplikasi e-iANC acceptable atau dapat diterima pengguna akhir dan dalam grade A dan B dengan rating excellent. Hal ini berarti aplikasi e-iANC dapat terus dikembangkan dan dijadikan alat bantu bidan dalam melakukan ANC.Kata Kunci: Electronic Integrated Antenatal Care, e-iANC, System Usability Scale (SUS), bidan